Entre águas e gentes : vivências e (in)visibilidades nos territórios do litoral de Sergipe - Santos, Rodrigo Herles dos (2015)
This research addresses the territorial formation of the Coast Sergipe. This space was historically constituted and socially appropriate. The first aim is to reflect on the traditional community space in view of its constitution as a territorial formation, checking the spaces, referred to by residents and their articulation in the formation of social and territorial identities in the Coast. In terms of methodology, our choice was up by qualitative approach, whose research framework, gives grip to the relational nature and phenomenal interactions between nature, culture, space and territory we explored. The development of the thesis was initiated by the constitution of the theoretical elements of the categories used in the analysis, especially the discussion of territory, identity and representation. Following, we established an analysis of historical facts and processes that help to understand the territorial formation of Sergipe more broadly and, the Coastline, so more specific, focusing on the establishment of traditional fishing communities. At this point, we are interested in providing elements for understanding how the traditional population, generally excluded from political and economic processes hegemonic occupied rare and valued environments of Sergipe territory. The appropriation process of space and its representation was analyzed taking into account the spatial elements referenced by the subjects of the Coastline. Therefore, we set our research locus in three traditional communities of Terra Caída , Pedreiras e Tigre/Junça between the south, center and north, respectively. We adopt procedures and research instruments to capture the representation of the territory in each community, taking into account the distribution among children and youth, adults and seniors. In this sense, we examine the constitution of the identities of the subjects, the narrative of his historicity with your experience space and reference, and, We verify the existence of identity with the spaces and coastal environments. The relationship between identity and territory is expressed in the prospect of staying in the territory, as an act and a sense of permanence and rooting what belongs to me to the same extent that I belong to that territory. Finally, between the refuge condition in empty coastline and home established in the territories we reflect on the identities and territories of traditional communities coastline of Sergipe between the experiences, work practices and invisibilities.